Perancangan Sistem Informasi PT.AMSA Berbasis Web Menggunakan Wordpress - Hermawan, Ervin, Heru Supriyono, ST. MSc. PhD (2016)
PT. AMSA is a company engaged in the field of health, the company that has been established since 2009, is engaged in the field of health, especially in orthopedic implant and instrument. The passage of time with the many requests of cooperation with various hospitals PT. AMSA requires online media eg website, making it easier to find information of companies to be invited to cooperation. Therefore, the authors create web-based information system for PT. AMSA so that counterparties or hospital is more easy to find the information. PT.AMSA in the design of the company's website using an application that is often used is wordpress. website focused on enterprise information melihatkan PT. AMSA such information within the company, its vision, mission, cooperation and news about the company PT. AMSA. of this study to provide the information system for PT. AMSA online. Qualitative taken for the research, which is the collection of data directly to the PT. AMSA. tests performed were able to demonstrate the existence of information systems based on the company's website greatly helped in conveying information products that can be accessed in all places, so the website is able to resolve the problem.